2005
DOI: 10.1080/08035250510028740
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial comparing beractant and poractant treatment in neonatal respiratory distress syndrome

Abstract: Infants with RDS treated with poractant had a lower FiO2 requirement during the first 48 h compared to infants who received beractant. Infants who received poractant also had fewer PDAs than infants who received beractant. The difference in FiO2 was not associated with a difference in age of first extubation, total intubation time, or incidence of bronchopulmonary dysplasia between groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 25 publications
5
54
0
1
Order By: Relevance
“…This is a highly selected population of very premature infants who were mechanically ventilated for RDS, infants with the greatest risk of developing the morbidities of prematurity, including PDAs and chronic lung disease. Our observation extends the findings of Malloy et al 5 who also found a lower incidence of PDAs in infants treated with poractant alfa, compared with beractanttreated infants.…”
Section: Discussionsupporting
confidence: 91%
“…This is a highly selected population of very premature infants who were mechanically ventilated for RDS, infants with the greatest risk of developing the morbidities of prematurity, including PDAs and chronic lung disease. Our observation extends the findings of Malloy et al 5 who also found a lower incidence of PDAs in infants treated with poractant alfa, compared with beractanttreated infants.…”
Section: Discussionsupporting
confidence: 91%
“…In the study by Ramanathan et al 27 both doses of poractant alfa (100 mg kg À1 and 200 mg kg À1 ) were compared with one dose of beractant (100 mg kg À1 ) and neonatal mortality was lowest in the higher dose poractant alfa group (3%) versus lower dose poractant alfa (6%) and beractant (8%). Similar reductions in mortality have been found in other trials that used a 200 mg kg À1 initial dose 32,33 (Table 3). If the Ramanathan et al study is taken to report two separate trials, beractant versus two groups of poractant alfa-treated infants, then six comparative trials of these two natural surfactants can be considered with a total of 20 deaths in the poractant alfa group and 33 in the beractant group (Table 3).…”
supporting
confidence: 85%
“…In a meta-analysis of the two studies 23,25 comparing beractant vs poractant alfa, neonatal mortality was significantly lower with poractant alfa (odds ratio 0.35, 95% CI 0.13, 0.92). In a recent study comparing these two surfactants, Malloy et al 26 extended the observations of Ramanathan et al 25 They showed improvement in oxygenation to persist up to 48 h ( Figure 1) 26 after treatment with poractant alfa, and a significantly lower number of additional doses with poractant alfa compared to beractant. It is also interesting to note that the use of a higher initial dose of poractant alfa at 200 mg/kg vs 100 mg/kg of beractant in three comparison trials have consistently shown a lower mortality favoring poractant alfa (Figure 2).…”
Section: Introductionmentioning
confidence: 64%
“…It is also interesting to note that the use of a higher initial dose of poractant alfa at 200 mg/kg vs 100 mg/kg of beractant in three comparison trials have consistently shown a lower mortality favoring poractant alfa (Figure 2). 23,25,26 This observation may have been due to a larger dose of a more effective surfactant moderating disease severity during the acute phase of RDS in these ill preterm infants, thus resulting in a better survival. However, none of these trials was powered to evaluate mortality as a primary outcome.…”
Section: Introductionmentioning
confidence: 99%